Towards group communication for mobile participants. - MEIER, RENE; CAHILL, VINNY (My University, 2001)
Group communication will undoubtedly be a useful paradigm for many applications of wireless networking in which reliability and timeliness are requirements. Moreover, location awareness is clearly central to mobile applications such as trac management and smart spaces. In this paper, we introduce our definition of proximity groups in which group membership depends on location and then discuss some requirements for a group membership management service suitable for proximity groups. We describe a novel approach to efficient coverage estimation, giving applications feedback on the proportion of the area of interest covered by a proximity group, and also discuss our approach to partition anticipation.
Proceedings of ACM Workshop on Principles of Mobile Computing (POMC)
ACM Workshop on Principles of Mobile Computing (POMC)
PUBLISHED
Keywords: Computer Science